PERAN PEMERINTAH DESA DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA DI PANTAI GUMUK KANTONG DESA SUMBERSEWU KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Putri Indrayani; Sri Wilujeng; Herwin Kurniadi (Journal of Innovation Research and Knowledge, 2025)
Gumuk kantong beach in sumbersewu village, muncar district, banyuwangi regency, is a tourist attraction that has biodiversity and beautiful natural views, and plays an important role in improving the local economy and protecting the coastal environment. However, the management of this tourist attraction faces several challenges, such as a lack of financial contributions from the village government, low community participation, as well as a lack of facilities and awareness of the importance of environmental conservation. The village government, through law of the republic of indonesia number 03 of 2024 and banyuwangi regency regional regulation number 02 of 2024, seeks to improve ecotourism management in this area by involving local communities in the sustainable management and development of tourist attractions. In 2022, management of gumuk kantong beach will begin with the formation of a tourism awareness group (pokdarwis) and governance training. Even though there has been significant progress, greater efforts are still needed to increase public awareness and better supporting facilities, in order to maintain the sustainability of the ecosystem and improve the quality of tourism management. This research aims to explore the role of village government and community participation in managing the gumuk kantong beach tourist attraction, as well as the challenges and opportunities faced in maximizing the potential of this natural tourism. Objective: to find out and describe the role of the village government and community participation in managing tourist attractions on gumuk kntong beach, sumbersewu village, muncar district, banyuwangi regency. The research method is qualitative and is a type of descriptive research. The role of village government is focused on the ideas of siagian (2009:142-150) 1) government as stabilizer, 2) government as innovator, 3) govermentas pioneer, and 4) government as modernizer, and this community participation is focused anthe idea of patrolling (2021:146) Community empowerment aims to improve the local economy and protect the coast. Routine evaluations are carried out to ensure optimal management. The main objective of developing this tourist attraction is to empower the community, improve the economy, and introduce gumuk kantong beach to the international market.